2005
DOI: 10.1055/s-2004-830381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Whole Body Vibration Training on Muscle Strength and Sprint Performance in Sprint-Trained Athletes

Abstract: Despite the expanding use of Whole Body Vibration training among athletes, it is not known whether adding Whole Body Vibration training to the conventional training of sprint-trained athletes will improve speed-strength performance. Twenty experienced sprint-trained athletes (13 male symbol, 7 female symbol, 17-30 years old) were randomly assigned to a Whole Body Vibration group (n=10: 6 male symbol and 4 female symbol) or a Control group (n=10: 7 male symbol, 3 female symbol). During a 5-week experimental per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
1
27

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 22 publications
6
91
1
27
Order By: Relevance
“…There have been reports that WBV training does not have an effect on shuttle-run (Torvinen et al, 2002b), sprinting speed (Delecluse, Roelants, Diels, Koninckx, & Verschueren, 2005) or agility performance (Cochrane, Legg, & Hooker, 2004). In contrast, other studies have reported that WBV positively influenced TUG (Schuhfried, Mittermaier, Jovanovic, Pieber, & Paternostro-Sluga, 2005), Tinetti test (Bautmans et al, 2005;Bruyere et al, 2005), and balance (Torvinen et al, 2002a).…”
Section: Discussionmentioning
confidence: 85%
“…There have been reports that WBV training does not have an effect on shuttle-run (Torvinen et al, 2002b), sprinting speed (Delecluse, Roelants, Diels, Koninckx, & Verschueren, 2005) or agility performance (Cochrane, Legg, & Hooker, 2004). In contrast, other studies have reported that WBV positively influenced TUG (Schuhfried, Mittermaier, Jovanovic, Pieber, & Paternostro-Sluga, 2005), Tinetti test (Bautmans et al, 2005;Bruyere et al, 2005), and balance (Torvinen et al, 2002a).…”
Section: Discussionmentioning
confidence: 85%
“…Another explanation is that the training was not intense or long enough. However, the training protocol used in this study was similar to that of other WBV studies 14,24,25 and decided after literature search and discussions with a person with experience of WBV training in rehabilitation. Training twice weekly is also a common frequency at private gyms and in public health care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Overall it appears the literature demonstrates a positive effect of WBV on jumping performance with several short term cumulative effect studies (10 days-8 weeks) have noted improvements in jump height (4,6,7,13,15,26,33) whilst a few have noted no improvements (11,12,23). In relation to dance training the studies by Wyon and colleagues (33) and Aninno and colleagues (4) both noted increases in jump height as well as no significant changes in leg anthropometry and significant increases in knee extensor strength respectively.…”
Section: Introductionmentioning
confidence: 99%